Effectiveness of Participatory Extension on Farmers' Knowledge, Attitude, and Skills in Using Beauveria bassiana for Rice Bug Control - Eny Wahyuning Purwanti; Himmata Suryanit; Suryaman Sule (Jurnal Penyuluhan, 2026)
This study aimed to determine the effectiveness of a participatory extension approach in promoting the utilization of the entomopathogenic fungus Beauveria bassiana as a biological control agent for rice bug infestation in rice fields. A quasi-experimental design with pretest-posttest measurement was employed, utilizing participatory action research methodology. The participatory extension process involved the identification of local potential, collaborative planning with farmers, and farmer-inclusive evaluation, utilizing the POAC (Planning, Organizing, Actuating, Controlling) management cycle. The intervention targeted members of the Rukun Tani Farmer Group, with extension materials sourced from literature review and applied research. The "Demonstration Plot" method was employed, using folders and real objects as media. Data were collected through knowledge tests (pre-post), attitude questionnaires, and skill observation checklists. Extension effectiveness was evaluated by measuring farmers' increase in knowledge, attitude level, and skills regarding the application of B. bassiana. Evaluation results demonstrated a significant difference in the level of knowledge before and after the extension. Attitude evaluation yielded an average score of 88.45%, falling into the positive category, which indicated a high level of interest from the target group in the material presented. Furthermore, the skill evaluation, assessed using an observation checklist, concluded that farmers’ skills in applying B. bassiana were in the high category. These findings suggest that the participatory extension approach effectively enhanced farmers’ adoption of this environmentally friendly pest control technology.